2011
DOI: 10.4314/ejhd.v24i3.68379
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and variation of traffic air pollution as measured by CO in the City of Addis Ababa, Ethiopia

Abstract: Background: Air pollution level in Addis Ababa is presumed to be high due to the prevalence of old vehicles and substandard road infrastructures. This study assessed CO concentration as a measure of traffic air pollution. Materials and methods: a total of 80 road side and 24 on-road daily traffic air samples during wet and dry seasons of 2007 and 2008, respectively, were taken using CO data logger. A structured checklist was used to document related data. Downloaded data from the CO sampler was used to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…All the sites (SS16, SS40, SS3, SS41, SS33, SS39, SS38, SS26 and SS35) with high CO concentration (mean ± SD) are sites located in the high congestion traffic zones of Addis Ababa. The finding of this study is higher than the value reported (2.8 and 2.1 ppm in dry and wet seasons respectively) by [3] which was studied in the same city (Addis Ababa) and lower than the one reported by [16]. The higher concentration of CO recorded in this research work was may be due to the indirectly increased vehicle congestion in the city.…”
Section: Roadsides Co Concentrationcontrasting
confidence: 87%
See 3 more Smart Citations
“…All the sites (SS16, SS40, SS3, SS41, SS33, SS39, SS38, SS26 and SS35) with high CO concentration (mean ± SD) are sites located in the high congestion traffic zones of Addis Ababa. The finding of this study is higher than the value reported (2.8 and 2.1 ppm in dry and wet seasons respectively) by [3] which was studied in the same city (Addis Ababa) and lower than the one reported by [16]. The higher concentration of CO recorded in this research work was may be due to the indirectly increased vehicle congestion in the city.…”
Section: Roadsides Co Concentrationcontrasting
confidence: 87%
“…The daily (hourly) maximum CO concentration recorded during the study period was 18 ppm for SS14 and SS3 sampling sites on rushing hours of the day on 9:00 am and 5:00 pm respectively [ Figure 4]. The high CO concentration in the early morning and late afternoon was due to the congested vehicular staging and stagnation of temperature in the city [3,16]. The low concentration of CO at mid-day was because of the photochemical reaction taking place by sunlight in the presence of hydrocarbons as CO is converted to carbon dioxide [3].…”
Section: Roadsides Co Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Private vehicles account for 30% of the total demand for transportation, while the rest of the demand is met largely by auto-rickshaws and taxis. Reddy and Venkataraman [7] and Abera et al [8] note that the pollutants like CO and NO x emanate from automobile exhausts, whereas use of coal based fuels causes heavy emissions of SO 2 . Murphy (2008) et al [2] and Rosibeto et al [9] find that the levels of O 3 , NO x and particulate matter are an issue of concern in the urban environment.…”
Section: Pollution Emissionmentioning
confidence: 99%